PENDIDIKAN KEWARGANEGARAAN BERBASIS LITERASI DIGITAL: SUATU ALTERNATIF PEMBELAJARAN KARAKTER MENUMBUHKAN KEADABAN KEWARGAAN - Kusnadi Kusnadi (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2023)
ABSTRACT Citizenship Education is held to shape the character and personality of the community by the values ​​of Pancasila. Citizenship education must reach all levels of society through information and communication technology. The quality of learning for Citizenship Education is one of the educational challenges that must be faced. Learning that involves students' activeness in the learning process is an effort to improve the quality of education. Learner-centred learning can create a system that supports students in engaging in a more attractive, dynamic, and varied learning experience. With advances in information and communication technology, efforts to improve learning can be carried out through attitudes in responding to the quality of technology application in a digital-based system known as digital literacy. The method used in the analysis of this discussion is a literature study. In this article, we discuss Digital Literacy as a Technological Competency, Citizenship Education as a vehicle for character education, and Digital Literacy-Based Citizenship Education Learning in Fostering Citizenship Civilization as National Character.